2004
DOI: 10.1093/pasj/56.5.l29
|View full text |Cite
|
Sign up to set email alerts
|

Probing Warm-Hot Intergalactic Medium Associated with the Virgo Cluster Using an Oxygen Absorption Line

Abstract: To detect a warm-hot intergalactic medium associated with the large-scale structure of the universe, we observed a quasar behind the Virgo cluster with XMM-Newton. With a net exposure time of 54 ks, we marginally detected an O VIII Kα absorption line at 650.9 +0.8 −1.9 eV in the RGS spectra, with a statistical confidence of 96.4%. The observed line center energy is consistent with the redshift of M87, and hence the absorber is associated with the Virgo cluster. From the curve of growth, the O VIII column densi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…Marginal detection of O viii and Ne ix absorption features in XMM-Newton RGS spectra of distant quasars was reported in the vicinity of the Virgo and Coma clusters and interpreted as indication of the presence of dense and hot WHIM concentrations near the clusters (Fujimoto et al 2004;Takei et al 2007). A blind search for WHIM was performed by Nicastro et al (2005), who reported the discovery of two intervening systems at z > 0 in absorption along the line-of-sight to the blazar Mrk 421 in the Chandra Low Energy Transmission Grating Spectrometer (LETGS) spectra.…”
Section: Introductionmentioning
confidence: 92%
“…Marginal detection of O viii and Ne ix absorption features in XMM-Newton RGS spectra of distant quasars was reported in the vicinity of the Virgo and Coma clusters and interpreted as indication of the presence of dense and hot WHIM concentrations near the clusters (Fujimoto et al 2004;Takei et al 2007). A blind search for WHIM was performed by Nicastro et al (2005), who reported the discovery of two intervening systems at z > 0 in absorption along the line-of-sight to the blazar Mrk 421 in the Chandra Low Energy Transmission Grating Spectrometer (LETGS) spectra.…”
Section: Introductionmentioning
confidence: 92%
“…The properties of the WHIM in filaments of galaxies have been investigated before. For instance, the density of the WHIM in filaments has been deduced from observations of X-ray absorption lines (Takei et al 2002;Fujimoto et al 2004;Nicastro et al 2005; Kaastra et al 2006;Buote et al 2009;Fang et al 2010;Zappacosta et al 2010;Nicastro et al 2013). Up to now, however, X-ray emission from the WHIM has not been detected yet, due to limited sensitivities of X-ray spectrometers such as CCD cameras, except for reports of angular correlation of the diffuse X-ray background (Galeazzi et al 2009) and emission in a filament linking two clusters of galaxies (Werner et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Fujimoto et al (2004) attempted to detect absorption in the quasar LBQS 1228+1116, located behind the Virgo cluster. An XMM-Newton RGS spectrum revealed a marginal feature at the (Virgo) redshifted position of O VIII Lyα, but only at the ∼ 95% confidence level.…”
Section: Intervening Whim Absorbers At Low Redshiftmentioning
confidence: 99%